Fabrication of Si3N4–SiC/SiO2 composites using 3D printing and infiltration processing. Issue 20 (15th October 2021) - Yu, Siwen; Zeng, Tao; Pan, Xiaotong; Wu, Rina; Fan, Meiling; Xu, Guodong; Cheng, Su
Abstract: Si3 N4 –SiC/SiO2 composites were prepared by employing three-dimensional (3D) printing using selective laser sintering (SLS) and infiltration processing. The process was based on the infiltration of silica sol into porous SLS parts, and silicon carbide and silicon nitride particles were bonded by melted nano-sized silica particles. To optimize the manufacturing process, the phase compositions, microstructures, porosities, and flexural strengths of the Si3 N4 –SiC/SiO2 composites prepared at different heat-treatment temperatures and infiltration times were compared. Furthermore, the effects of the SiC mass fraction and the addition of Al2 O3 and mullite fibers on the properties of the Si3 N4 –SiC/SiO2 composites were investigated. After repeated infiltration and heat treatment, the flexural strength of the 3D-printed Si3 N4 –SiC/SiO2 composite increased significantly to 76.48 MPa. Thus, a Si3 N4 –SiC/SiO2 composite part with a complex structure was successfully manufactured by SLS and infiltration processes.